The protective effect of rs373863828 on type 2 diabetes does not operate through a body composition pathway in adult Samoans. Issue 12 (25th October 2022) - Hawley, Nicola L.; Duckham, Rachel L.; Carlson, Jenna C.; Naseri, Take; Reupena, Muagututia Sefuiva; Lameko, Viali; Pomer, Alysa; Wetzel, Abigail; Selu, Melania; Lupematisila, Vaimoana; Unasa, Folla; Vesi, Lupesina; et al.
Abstract: Objective: The aim of this study was to understand whether the paradoxical association of missense variant rs373863828 in CREB3 regulatory factor ( CREBRF ) with higher BMI but lower odds of diabetes is explained by either metabolically favorable body fat distribution or greater fat‐free mass. Methods: This study explored the association of the minor allele with dual‐energy x‐ray absorptiometry‐derived body composition in n  = 421 Samoans and used path analysis to examine the mediating role of fat and fat‐free mass on the relationship between rs373863828 and fasting glucose. Results: Among females, the rs373863828 minor A allele was associated with greater BMI. There was no association of genotype with percent body fat, visceral adiposity, or fat distribution in either sex. In both females and males, lean mass was greater with each A allele: 2.16 kg/copy ( p  = 0.0001) and 1.73 kg/copy ( p  = 0.02), respectively. Path analysis showed a direct negative effect of rs373863828 genotype on fasting glucose ( p  = 0.004) consistent with previous findings, but also an indirect positive effect on fasting glucose operating through fat‐free mass ( p  = 0.027). Conclusions: The protective effect of rs373863828 in CREBRF, common among Pacific Islanders, on type 2 diabetes does not operate through body composition. Rather, the variant's effects on body size/composition and fasting glucose likely operate via different, tissue‐specific mechanisms.